BEDAH INFLASI KOTA SEMARANG DI MASA PANDEMI - Lilis Anisah (Jurnal Riptek, 2021)
Low and stable inflation is a prerequisite for sustainable economic growth aimed at improving people's welfare. This study aims to provide an overview of the development of inflation in the Semarang City, compared to Central Java Province and national during 2020 which was the year of the Covid-19 pandemic. The results of the study show that the group expenditure on food, beverages, and tobacco; and the personal care and other service expenditure group is the expenditure group that most frequently experiences the highest monthly inflation or the lowest deflation in Semarang City on 2020. The results of the study is expected to be valuable information for the government, private sector and the monetary authority holders (Bank Indonesia) who related to the issue of price stability. It is expected to be a useful source of information for various good purposes in the future.